Análise espacial e temporal da transmissão da dengue e caracterização do processo endêmico no município de São José do Rio Preto, SP - Mondini, Adriano (2005)
The use of spatial analysis tools is an important instrument to understanding dengue incidences in different areas of the municipality and providing important information for the risk stratification and the optimization of control and vigilance tools. This study aimed at performing a spatial and a temporal analysis on dengue transmission in a medium-sized city in the interior of the State of Sao Paulo, Brazil, covering the period from September 1994 to August 2002. Autochthonous cases with confirmation by laboratory tests were utilized. Population data on the city of Sao Jose do Rio Preto were obtained from the Brazilian Institute for Geography and Statistics and the municipal authorities. The cases were georeferenced according to street addresses and clustered according to the 432 census tracts in the municipality, thus resulting in thematic maps. The analysis of main components generated a factor which was used to divide the municipality in four distinct groups, according to socioeconomic level. Moran Index was calculated through multiple regressions of socioeconomic variables. Georeferencing, spatial analysis and the confection of maps were performed through ArcGis tools. A rising trend in annual incidence was noted, with a peak in 2000/2001. From 1990 to 1994 the length of the transmission period reached a maximum of five months per year. This period increased in length over subsequent years. In the final year investigated, transmission occurred in all twelve months, without interruptions. In the period of study 94-95, the socioeconomic component was relevant in dengue incidences. The risk of getting infected in class-4 sites was 2,7 times bigger than in class-1 areas in this period. Not only socioeconomic variables were responsible for dengue incidences in the municipality, but also demographic and environmental characteristics. The endemic pattern of the transmission and the differentiated occurrence according to areas need to be taken into account when developing strategies for dengue control. It is important to stand out that spatial patterns are very important in the risk of dengue transmission. However, several variables are intimately linked with the modulation of disease dynamics, such as circulating serotypes in the municipality and the immunity level of resident population, socioeconomic factors, mosquito infestation, among others, demonstrating that dengue incidences cannot be interpreted in an unilateral form, but contemplated in an holistic way.